PENGARUH LATIHAN SQUAT MENGGUNAKAN RESISTANCE BAND TERHADAP KEMAMPUAN SHOOTING SEPAK BOLA - Aldi Firansyah; Irsan Kahar; Rahmatia Rahmatia (Jurnal Pendidikan Olah Raga, 2023)
Football is a very popular sport in society. Anyone can play this sport because it doesn't require a lot of money to play it. The problem in this study is that hitting athletes is still far from what is expected, because the many punches made by athletes both in matches and practice show that only a few can hit the target. The purpose of this study was to determine the effect of different forms of squats and resistance bands on the shooting performance of Bmd Olang Fc athletes. The method used in this research is experimental research with quantitative data collection. The population of this study consisted of 15 Bmd Olang Fc athletes. The sampling technique used in this study was pretest and posttest. In this study, 15 athletes from Bmd Olang Fc. Data analysis with t-test. The research results obtained showed that the average T-score before the test was 42.40 and the average result after the test was 57.20. The average after the test was higher than before the test, meaning that the squatting group's resistance affected the shooting ability. From this it can be concluded that squat training with resistance bands has a significant effect on shooting in soccer games.